Persepsi Guru terhadap Penggunaan Media Sosial dalam Pembelajaran Pendidikan Agama Islam di SMA Negeri 2 Sukoharjo - Khairunnisa, Afifah; Abidin, Zaenal (Cetta: Jurnal Ilmu Pendidikan, 2025)
The advancement of information and communication technology (ICT), particularly through social media, has expanded across many sectors, including education. Social media offers new possibilities for teaching Islamic Religious Education (PAI), particularly in improving access to learning materials and facilitating interactions between educators and students. However, the use of social media also brings challenges, such as the potential spread of misinformation. This study aims to explore teachers' perceptions of using social media in PAI instruction and to identify the advantages and challenges of its implementation at SMA N 2 Sukoharjo. The research adopts a phenomenological approach with a qualitative design. Data collection was conducted through in-depth interviews, observations, and document analysis. The data were analyzed through reduction, presentation, and conclusion drawing. Triangulation techniques were used to ensure the validity of the data. The findings show that the use of social media in PAI teaching at SMA N 2 Sukoharjo has been met with positive feedback. Platforms such as blogs, WhatsApp, YouTube, and Instagram were seen as effective tools for enhancing student engagement and comprehension. Nevertheless, challenges remain, including monitoring students' access to content and the dependency on social media, which can distract from the learning process. In conclusion, while social media presents notable benefits for PAI teaching, teachers must actively guide and oversee its use to ensure the content aligns with Islamic values.